Is long‐term survival possible after margin‐positive resection of retroperitoneal sarcoma (RPS)?. Issue 7 (6th April 2016) - Klooster, Brittany; Rajeev, Rahul; Chrabaszcz, Sarah; Charlson, John; Miura, John; Bedi, Meena; Gamblin, Thomas Clark; Johnston, Fabian; Turaga, Kiran K.
Abstract : Background/Objectives: For various reasons, some patients undergo a gross margin positive resection (R2) leading to a dilemma in care. We hypothesized that there is a subset of patients who have long‐term survival (LTS, ≥5 years) after R2 resection for retroperitoneal sarcoma (RPS). Methods: National Cancer Database data from 1998 to 2011 were reviewed to identify patients with RPS who had R2 resections. Logistic and Cox regression models were used to compare LTS with short‐term survival. Results: Of 12, 028 patients, R2 resection rate was 3.28% (4.9% in 1998; 2.5% in 2011). Median survival for RPS with R2 resection was 21 months versus 69 months for those with R0/R1 resections ( P  < 0.001). Of 272 patients with available survival, 24% (n = 64) survived ≥5 years with 64% alive at follow‐up. LTS was most often seen in younger patients (<65 years) with well‐differentiated liposarcoma. Chemotherapy appeared to improve survival in the first 3 postoperative years, but paradoxical effects were seen in LTS (Hazards Ratio [HR] 0.69, 95%CI: 0.50–0.95, P  = 0.024) in first 3 years versus (HR 2.15, 95%CI: 1.21–3.81, P  = 0.009). Conclusion: Long‐term survival is possible for a subset of patients after an R2 resection for RPS, especially with favorable histology characteristics. Benefits of chemotherapy in margin positive settings need to be investigated. J. Surg. Oncol. 2016;113:823–827 . © 2016 Wiley Periodicals, Inc.